The impact of the Asian economic crisis on the tourism industry in Singapore. - Heng, Anna Quee Ying. (2008)
The objective of this research aims to investigate the impact of the Asian economic crisis on some of the different tourism sectors, namely the hotel industry, the travel agent industry and the attraction industry. In addition, research is also conducted to find out the motivational factors of overseas visitors in choosing Singapore as a holiday destination, as well as the various forms of promotions undertaken by the Singapore Tourism Board (STB).